The Life of Saidakhmad Vasli Samarkandi and His Role in the Literary Environment in that Time (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the life of Sayidakhmad Vasli Samarkandi and his place in the literary environment are described in more detail from the point of view of modern literary science. Saydahmad Vasli, a teacher from Samarkand, said that he had creative relations with famous poets of his time, such as Zokirjon Furkat, Khamza Khakimzoda Niyazi, Kami Tashkandi, Mir Sarvar Urguti, Naqis Kattakurgani, and Salahiddin Makhdum-Salahi. The fact that Vasli Samarkandi had close and friendly relations with the enlighteners of his time and that he created in harmony with their work is manifested as an enlightened, inquisitive, patriotic person.